O direito constitucional e os direitos humanos como reguladores da atuação das empresas transnacionais - Vailatti, Diogo Basilio (2016)
This paper focuses on the analysis of the regulatory system of Transnational Corporations. Therefore, the research is divided into three chapters. The first chapter checks the expansion of the human rights system, which resulted in the supremacy of Constitutional Law and Human Rights. The second chapter examines how the State is essential to act to regulate the economy, in particular in relation to transnational corporations. The third chapter, drawing on the assumptions outlined in the previous chapters, seeks to indicate the regulatory system performance of Transnational Corporations by the thread of Constitutional Law and Human Rights. As for the research techniques, the paper uses the literature and document analysis. In relation to the methods, the work draws on the hypothetical-deductive method.